PENGARUH FAKTOR PRIBADI TERHADAP KEPUTUSAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TADULAKO MEMBELI SMARTPHONE XIAOMI - FATIMA, SITI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2020)
The purpose of this study was to determine the Effect of Personal Factors on the Decision of the Students of the Faculty of Economics, Tadulako University, to buy a Xiaomi Smartphone in the City of Palu. The sampling technique uses incidental sampling with the number 75. The data used in this study are primary data obtained by providing a list of questions (questionnaire). The analytical method used is multiple linear regression analysis, F test and t test. The results showed (1) the age variable and stage in the life cycle had a significant effect on the Decision of the Faculty of Economics Students of Tadulako University to buy a Xiaomi Smartphone in Palu City (2) the work variable had a significant effect on the Decision of the Faculty of Economics Students in Tadulako to buy a Xiaomi Smartphone in Palu City (3) lifestyle influences significantly on the Decision Faculty of Economics Students to buy a Xiaomi Smartphone in Palu City (4) personality variables and self-concept have a significant effect on the Decision of the Faculty of Economics Students in to buy a Xiaomi Smartphone in Palu City.